TENCON 2003. Conference on Convergent Technologies for Asia-Pacific Region
DOI: 10.1109/tencon.2003.1273164
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy-neural approach to electricity load and spot price forecasting in a deregulated electricity market

Abstract: attention. Although long term and short tcrm electric load forecasting has bccn of interest to the practicing engineers and researchers for many years, spot-price prediction is a relatively new research area. This paper examines the use of a neural-fuzzy infcrence nicthod for the prediction of 24 hourly load and spot price for the next day. Publicly available data of thc electricity inarket of the state of New South Walcs, Australia is used in a casc study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 5 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Then, first NN approaches were proposed (Wang and Ramsay, 1997) and applied for the existing energy pools. They were followed by different structures on NNs (Mendes et al, 2007;Yang and Sun, 2008;Akole et al, 2011), radial basis functions (Meng et al, 2009), recursive NNs (Mandal et al, 2007) and hybrid approaches of fuzzy NNs (Iyer et al, 2003) and with wavelets (Giri et al, 2010). Reports show that hybrid approach of wavelets and NNs called AWNN (Bhaskar and Singh, 2012) is an interesting alternative.…”
Section: Electricity Prices Prediction Taskmentioning
confidence: 99%
“…Then, first NN approaches were proposed (Wang and Ramsay, 1997) and applied for the existing energy pools. They were followed by different structures on NNs (Mendes et al, 2007;Yang and Sun, 2008;Akole et al, 2011), radial basis functions (Meng et al, 2009), recursive NNs (Mandal et al, 2007) and hybrid approaches of fuzzy NNs (Iyer et al, 2003) and with wavelets (Giri et al, 2010). Reports show that hybrid approach of wavelets and NNs called AWNN (Bhaskar and Singh, 2012) is an interesting alternative.…”
Section: Electricity Prices Prediction Taskmentioning
confidence: 99%
“…The extant literature also shows that there are multiple similarities between variable pricing electricity market and variable pricing cloud computing. The auction based cloud model has been influenced extensively by variable pricing electricity market [9][10][11][12][13]. There are multiple of similarities among the above mentioned markets.…”
Section: Background Of Auction Based Cloud Modelmentioning
confidence: 99%
“…(i) statistical models [1,2,6] (ii) artificial neural network (ANN) [3][4][5][6][7][8] Espinola, et al presented dynamic regression and transfer function models in California and Spanish markets [1]. They demonstrated that their methods gave better prediction accuracy than the ARIMA model.…”
Section: Introductionmentioning
confidence: 99%
“…They employed the three-layer perceptron as ANN. Afterwards, ANN and/or fuzzy inference based methods have been developed [5][6][7][8]. However, the conventional methods have a drawback that they are inclined to give larger prediction error due to high volatility of nonlinear time series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation